A Novel Technique for the Assessment of Preoperative Cardiovascular Risk: Reactive Hyperemic Response to Short-Term Exercise. (10th April 2013) - Schier, Robert; Hinkelbein, Jochen; Marcus, Hanke; Smallwood, Ashley; Correa, Arlene M.; Mehran, Reza; El-Zein, Randa; Riedel, Bernhard
Abstract : Background . Perioperative vascular function has been widely studied using noninvasive techniques that measure reactive hyperemia as a surrogate marker of vascular function. However, studies are limited to a static setting with patients tested at rest. We hypothesized that exercise would increase reactive hyperemia as measured by digital thermal monitoring (DTM) in association to patients' cardiometabolic risk. Methods . Thirty patients (58 ± 9 years) scheduled for noncardiac surgery were studied prospectively. Preoperatively, temperature rebound (TR) following upper arm cuff occlusion was measured before and 10 minutes after exercise. Data are presented as means ± SD. Statistical analysis utilized ANOVA and Fisher's exact test, with P values <0.05 regarded as significant. Results . Following exercise, TR-derived parameters increased significantly (absolute: 0.53 ± 0.95 versus 0.04 ± 0.42 ∘ C, P=0.04, and % change: 1.78 ± 3.29 versus 0.14 ± 1.27 %, P=0.03 ). All patients with preoperative cardiac risk factors had a change in TR (after/before exercise, ΔTR) with values falling in the lower two tertiles of the study population (Δ TR < 1.1 %). Conclusion . Exercise increased the reactive hyperemic response to ischemia. This dynamic response was blunted in patients with cardiac risk factors. The usability of this short-term effect for the preoperative assessment of endothelial function warrants further study.